A study of customer satisfaction toward the service quality provided by SOCSO Rawang / Nadiah Mohd Sharif - Mohd Sharif, Nadiah (Faculty of Business and Management, 2010)
This research is about a study on relationship between service quality and customer satisfaction at SOCSO Rawang. Factor such as service quality and customer satisfaction have been identified in order to investigate whether or not these factors have a relationship with customer satisfaction. The purpose of this study to measure the level of customer satisfaction toward the service quality provide by SOCSO Rawang. The objective of this research (1) To identify the level of customer satisfaction toward service provide by SOCSO Rawang, (2) To rank the element of service quality toward customer satisfaction and (3) To find out the alternative way to increase the level of satisfaction of customer toward SOCSO. The survey is conducted at Rawang area. The sample size for this study is 30 of customers that have deals with SOCSO Rawang. Data obtained using two methods that are primary and secondary data. Respondent are required to answer the questionnaires that contain element that potentially have relationship with service quality and customer satisfaction. Data are analyzed using Reliability Test, Frequency and Descriptive Statistic through SPSS Program. Based on SPSS Program a clear findings and result is observed. The findings showed that most of the customers were moderately satisfied with the service provided to them and demographic profiles seem have no relationship with customer’s satisfaction. Recommendation and suggestions are put on how to improve and increase customer’s satisfaction on the services provided by SOCSO Rawang.